#### Answer

$a_{14}$ + $b_{12}$ = -51 + 58 = 7

#### Work Step by Step

From graph
First term $a_{1}$ = 1
Second term $a_{2}$ = -3
Third term $a_{3}$ = -7
Sequence = 1, -3, -7, . . . . .
Common difference (d) = -7 + 3 = -3 - 1 = -4
By formula $a_{n}$ = $a_{1}$ + (n-1) d
$a_{14}$ = 1 + ( 14 - 1)(-4) = 1 + (13$\times$-4) = 1 - 52 = -51
First term $b_{1}$ = 3
Second term $b_{2}$ = 8
Third term $b_{3}$ = 13
Sequence = 3, 8, 13, . . . . .
Common difference (d) = 13 - 8 = 8 - 3 = 5
By formula $b_{n}$ = $b_{1}$ + (n-1) d
$b_{12}$ = 3 + ( 12 - 1)5 = 3 + (11$\times$5) = 3 + 55 = 58
$a_{14}$ + $b_{12}$ = -51 + 58 = 7